2021
DOI: 10.3340/jkns.2021.0181
|View full text |Cite
|
Sign up to set email alerts
|

Flow Diverter Devices for the Treatment of Unruptured Vertebral Artery Dissecting Aneurysm

Abstract: Objective : Vertebral artery dissecting aneurysm (VADA) is a very rare subtype of intracranial aneurysms; when ruptured, it is associated with significantly high rates of morbidity and mortality. Despite several discussions and debates, the optimal treatment for VADA has not yet been established. In the last 10 years, flow diverter devices (FDD) have emerged as a challenging and new treatment method, and various clinical and radiological results have been reported about their safety and effectiveness. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…A multicenter study of 131 posterior circulation aneurysms showed that a pipeline embolization device (PED) was effective with an 89.7% complete or near complete occlusion rate for dissecting aneurysms [ 8 ]. In most recent, Kim et al [ 12 ] demonstrated a satisfied angiographic result within 3–6 months follow-up, which showed with 77.8% (7/9) complete or near complete VADA obliteration using FDS. Although one patient showed with segmental occlusion, the clinical outcome was mRS 0 in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter study of 131 posterior circulation aneurysms showed that a pipeline embolization device (PED) was effective with an 89.7% complete or near complete occlusion rate for dissecting aneurysms [ 8 ]. In most recent, Kim et al [ 12 ] demonstrated a satisfied angiographic result within 3–6 months follow-up, which showed with 77.8% (7/9) complete or near complete VADA obliteration using FDS. Although one patient showed with segmental occlusion, the clinical outcome was mRS 0 in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…There have recently been reports on the use of flow diverters in non-hemorrhagic vertebral artery dissections [ 14 , 15 ]. However, there have also been reports of stent occlusion and transient cranial nerve palsy when flow diverters were used [14] .…”
Section: Discussionmentioning
confidence: 99%
“…There have recently been reports on the use of flow diverters in non-hemorrhagic vertebral artery dissections [ 14 , 15 ]. However, there have also been reports of stent occlusion and transient cranial nerve palsy when flow diverters were used [14] . Flow-diverters are a relatively new therapeutic technology, and the number of reports of their use for treating non-hemorrhagic vertebral artery dissection is not great.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no established treatment approaches for unruptured dissecting aneurysms of the vertebral artery. Even if unruptured intracranial dissecting aneurysms of the vertebral artery have been thought to have a benign clinical course ( 2 , 5 10 ), the natural course of these dissections are still unknown and treatment guidelines remain controversial and debatable ( 5 , 11 , 12 ). Moreover, some researchers believed that the risk of bleeding from unruptured dissecting aneurysms of the vertebral artery was higher than previous reports ( 6 , 12 ).…”
Section: Introductionmentioning
confidence: 99%